NAVIGATING THE EVOLUTION OF ENGLISH LANGUAGE TEACHING: TRENDS, CHALLENGES, AND INNOVATIONS - Abdumutalibova Mohlaroyim Xabibullo qizi The student of Chirchik State Pedagogical University, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
English language teaching (ELT) has undergone significant transformations, reflecting broader changes in educational theory, technology, and global communication. As English continues to solidify its role as a global lingua franca, understanding the evolution of its teaching methodologies, addressing contemporary challenges, and embracing innovative practices becomes crucial for educators worldwide. This article delves into the historical progression of ELT, current challenges faced by educators, and the impact of technological advancements on language instruction.